Alterations in arterial CO2 rather than pH affect the kinetics of neurovascular coupling in humans. (29th June 2021) - Caldwell, Hannah G.; Howe, Connor A.; Hoiland, Ryan L.; Carr, Jay M.J.R.; Chalifoux, Carter J.; Brown, Courtney V.; Patrician, Alexander; Tremblay, Joshua C.; Panerai, Ronney B.; Robinson, Thompson G.; Minhas, Jatinder S.; Ainslie, Philip N.
Abstract : Key points: We investigated the influence of arterial P C O 2 ( P aC O 2 ) with and without acute experimental metabolic alkalosis on neurovascular coupling (NVC). We assessed stepwise iso‐oxic alterations in P aC O 2 prior to and following intravenous NaHCO3 to acutely elevate arterial pH and [HCO3 – ]. The NVC response was not altered following NaHCO3 between stepwise P aC O 2 stages; therefore, NVC is acutely mediated by P aC O 2 rather than the prevailing arterial [H + ]/pH. The NVC response was attenuated by 27–38% with −10 mmHg P aC O 2 and the absolute peak change was reduced by −19% with +10 mmHg P aC O 2 irrespective of acutely elevated arterial pH/[HCO3 – ]. The NVC kinetics (i.e. time to peak) were markedly slower with hypercapnia versus hypocapnia (24 ± 5 vs . 7 ± 5 s, respectively) likely indicating an influence of resting cerebrovascular tone on NVC responsiveness. Abstract: Elevations in cerebral metabolism necessitate appropriate coordinated and localized increases in cerebral blood flow (i.e. neurovascular coupling; NVC). Recent pre‐clinical work indicates that arterial P C O 2 ( P aC O 2 ) mediates NVC independently of arterial/extracellular pH; this has yet to be experimentally tested in humans. The goal of this study was to investigate the hypotheses that: (1) the NVC response would be unaffected by acute experimentally elevated arterial pH; rather, P aC O 2 would regulate any changes in NVC; and (2) stepwise respiratory alkalosis and acidosis would each progressively reduce the NVC response. Ten healthy males completed a standardized visual stimulus‐evoked NVC test during matched stepwise iso‐oxic alterations in P aC O 2 (hypocapnia: −5, −10 mmHg; hypercapnia: +5, +10 mmHg) prior to and following intravenous NaHCO3 (8.4%, 50 mEq/50 ml) that elevated arterial pH (7.406 ± 0.019 vs . 7.457 ± 0.029; P  < 0.001) and [HCO3 – ] (26.2 ± 1.5 vs . 29.3 ± 0.9 mEq/l; P  < 0.001). Although the NVC response was collectively attenuated by 27–38% with −10 mmHg P aC O 2 (stage post hoc : all P  < 0.05), this response was unaltered following NaHCO3 (all P  > 0.05) irrespective of the higher pH ( P  = 0.002) at each matched stage of P aC O 2 ( P  = 0.417). The absolute peak change was reduced by −19 ± 41% with +10 mmHg P aC O 2 irrespective of acutely elevated arterial pH/[HCO3 – ] (stage post hoc : P  = 0.022). The NVC kinetics (i.e. time to peak) were markedly slower with hypercapnia versus hypocapnia (24 ± 5 vs . 7 ± 5 s, respectively; stage effect: P  < 0.001). Overall, these findings indicate that temporal patterns in NVC are acutely regulated by P aC O 2 rather than arterial pH per se in the setting of acute metabolic alkalosis in humans. Key points: We investigated the influence of arterial P C O 2 ( P aC O 2 ) with and without acute experimental metabolic alkalosis on neurovascular coupling (NVC). We assessed stepwise iso‐oxic alterations in P aC O 2 prior to and following intravenous NaHCO3 to acutely elevate arterial pH and [HCO3 – ]. The NVC response was not altered following NaHCO3 between stepwise P aC O 2 stages; therefore, NVC is acutely mediated by P aC O 2 rather than the prevailing arterial [H + ]/pH. The NVC response was attenuated by 27–38% with −10 mmHg P aC O 2 and the absolute peak change was reduced by −19% with +10 mmHg P aC O 2 irrespective of acutely elevated arterial pH/[HCO3 – ]. The NVC kinetics (i.e. time to peak) were markedly slower with hypercapnia versus hypocapnia (24 ± 5 vs . 7 ± 5 s, respectively) likely indicating an influence of resting cerebrovascular tone on NVC responsiveness.